2017
DOI: 10.1016/j.sjbs.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

BmNPV-miR-415 up-regulates the expression of TOR2 via Bmo-miR-5738

Abstract: MicroRNAs (miRNAs) have emerged as key players in host–pathogen interaction and many virus-encoded miRNAs have been identified (computationally and/or experimentally) in a variety of organisms. A novel Bombyx mori nucleopolyhedrosis virus (BmNPV)-encoded miRNA miR-415 was previously identified through high-throughput sequencing. In this study, a BmNPV-miR-415 expression vector was constructed and transfected into BmN cells. The differentially expressed protein target of rapamycin isoform 2 (TOR2) was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Bmnpv-miR-3 is also a BmNPV-produced miRNA that could regulate the P6.9 protein and various viral proteins to escape the immune attack of host cells ( Singh et al, 2014 ). In addition to the direct regulation of multiple proteins, viral miRNAs can also indirectly regulate host miRNAs that can, in turn, regulate the protein expression ( Cao et al, 2017 ). BmNPV-miR-415 was also found that it could down-regulate the expression of Bmo-miR-5738 in BmN cells and indirectly affect the expression of TOR2 protein, which plays an important role in the growth and development of the host ( Cao et al, 2017 ).…”
Section: Regulation Of Bmnpv Infection In the Silkworm By Ncrnasmentioning
confidence: 99%
“…Bmnpv-miR-3 is also a BmNPV-produced miRNA that could regulate the P6.9 protein and various viral proteins to escape the immune attack of host cells ( Singh et al, 2014 ). In addition to the direct regulation of multiple proteins, viral miRNAs can also indirectly regulate host miRNAs that can, in turn, regulate the protein expression ( Cao et al, 2017 ). BmNPV-miR-415 was also found that it could down-regulate the expression of Bmo-miR-5738 in BmN cells and indirectly affect the expression of TOR2 protein, which plays an important role in the growth and development of the host ( Cao et al, 2017 ).…”
Section: Regulation Of Bmnpv Infection In the Silkworm By Ncrnasmentioning
confidence: 99%
“…TOR2, as a member of the phosphatidylinositol kinase-related kinase family, plays a critical role in metabolism, development, growth, and survival at the cellular and organism levels. Recently it has been revealed that TORE2 also upregulates the molting hormone 20E (Cao et al, 2017). Apoptosis in Sf9 cells due to the inhibition of miR-14 indicates that it is essential for constitutive cell survival.…”
Section: Viral Mirnas Exploit the Host Machinerymentioning
confidence: 99%
“…BmNPV-miR-1 downregulates the expression of the host GTP-binding nuclear protein Ran and results in a significant increase in viral load [11]. The expression of rapamycin isoform 2 ( tor2 ) is upregulated by BmNPV-miR-415 via Bmo-miR-5738, although tor2 is not a direct target gene of BmNPV-miR-415 [12]. SpltNPV-encoded miRNAs have been reported to downregulate nine host genes [13].…”
Section: Introductionmentioning
confidence: 99%